Increased number of mast cells in the bone marrow of chronic myeloid leukemia may herald the pending myeloid transformation—the mast cell is an indicator of myeloid transformation - Xu, Peipei; Zhang, Cuiling; Wang, Yushan; Wu, Hongyan; Cheng, Shuwen; Fan, Xiangshan; Zhang, Qiguo (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Tumor cells are surrounded by many inflammatory cells, including mast cells (MCs), which can secrete several classic proangiogenic factors, resulting in endothelial cell proliferation and angiogenesis. However, the researches of the number of MC and microvessel density (MVD) in the bone marrow in chronic myeloid leukemia (CML) are rare. In this study, we aimed to investigate the relationship between tryptase-positive MCs and MVD in the different phases of CML. Methods: Bone marrow samples of 61 patients with CML and 20 healthy donors were collected from 2007 to 2017. Antibodies against the endothelial cell marker CD34 and against tryptase were used in immunohistochemistry. The diagnosis and counting of tryptase-positive MC and microvessel in bone marrow was at ×400 magnification. Results: MVD in CML group was higher than which in the control group, and the blast phase (BP) group had a higher MVD than which in chronic phase (CP) group (P